REFLEXIONS ABOUT THE FUTURE OF JOURNALISM, THE UNIVERSITY AND MASS COMMUNICATIONS - Estremadoyro, Julio (2011)
The technological advances and the internet resources have a big influenceon journalism, the university and society development in general. They representreal challenges for its own existence. Nowadays, nothing is steady intechnology. Things change at such a rapid pace that what is trendy at presentcould tomorrow be hardly remembered. This article intends to show manyaspects involved with new realities, among them the disappearance of thepaper book (to the thrust of the digital book); the more and more importantcitizen journalism and the crisis of printed newspapers; the availability ofinformation as never before and their risks linked to the veracity and respectfor ethical principles.